Effects of spatial separation with better- ear listening on N1-P2 complex - ÇİPRUT, AYŞE AYÇA (ELSEVIER SCI LTD, 2021)
Objective: The purpose of this study was to determine better-ear listening effect on spatial separation with the N1-P2 complex. Methods: Twenty individuals with normal hearing participated in this study. The speech stimulus /ba/ was presented in front of the participant (0 degrees). Continuous Speech Noise (5 dB signal-to-noise ratio) was presented either in front of the participant (0 degrees), left-side (-90 degrees), or right-side (+ 90 degrees). N1-P2 complex has been recorded in quiet and three noisy conditions. Results: There was a remarkable effect of noise direction on N1, P2 latencies. When the noise was separated from the stimulus, N1 and P2 latency increased in terms of when noise was co-located with the stimulus. There was no statistically significant difference in N1-P2 amplitudes between the stimulus-only and co-located condition. N1-P2 amplitude was increased when the noise came from the sides, according to the stimulus-only and co-located conditions. Conclusion: These findings demonstrate that the latency shifts on N1-P2 complex explain cortical mechanisms of spatial separation in better-ear listening. (C) 2021 Oto-Rhino-Laryngological Society of Japan Inc. Published by Elsevier B.V. All rights reserved.
Keywords: N1-P2 complex; Spatial separation; Better-ear listening; Head-shadow effect; Spatial release from masking; SPEECH-RECEPTION THRESHOLD; INDUCED INTERAURAL TIME; BROAD-BAND NOISE; COCKTAIL-PARTY; MISMATCH NEGATIVITY; LEVEL DIFFERENCES; VERTICAL-BAR; MASKING; RELEASE; HEARING